2019
DOI: 10.1136/gutjnl-2018-317612
|View full text |Cite
|
Sign up to set email alerts
|

Integrated paired-end enhancer profiling and whole-genome sequencing reveals recurrentCCNE1andIGF2enhancer hijacking in primary gastric adenocarcinoma

Abstract: ObjectiveGenomic structural variations (SVs) causing rewiring of cis-regulatory elements remain largely unexplored in gastric cancer (GC). To identify SVs affecting enhancer elements in GC (enhancer-based SVs), we integrated epigenomic enhancer profiles revealed by paired-end H3K27ac ChIP-sequencing from primary GCs with tumour whole-genome sequencing (WGS) data (PeNChIP-seq/WGS).DesignWe applied PeNChIP-seq to 11 primary GCs and matched normal tissues combined with WGS profiles of >200 GCs. Epigenome profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Aberrant chromatin structures are associated with the regulation of gene expression, and these chromatin structures are detected in cancer [14, 15]. Recent studies revealed long-range chromatin interaction in regions related to genomic rearrangements [16]. Genomic rearrangements are involved in “enhancer hijacking,” promoting the expression of CCNE1 and IGF2 .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant chromatin structures are associated with the regulation of gene expression, and these chromatin structures are detected in cancer [14, 15]. Recent studies revealed long-range chromatin interaction in regions related to genomic rearrangements [16]. Genomic rearrangements are involved in “enhancer hijacking,” promoting the expression of CCNE1 and IGF2 .…”
Section: Introductionmentioning
confidence: 99%
“…Super-enhancers tend to be preferentially insulated by strong boundaries to keep away from genes in adjacent TADs [ 38 ]. Enhancer-hijacking is considered a rare event and a mechanism exploited by genomic rearrangements [ 125 , 127 ]. For many genes, structural variants are remarkably related to elevated numbers or greater proximity of enhancer regulatory elements near the gene [ 3 , 127 ].…”
Section: Carcinogenic Mechanism Of Structural Variationmentioning
confidence: 99%
“…Enhancer-hijacking is considered a rare event and a mechanism exploited by genomic rearrangements [ 125 , 127 ]. For many genes, structural variants are remarkably related to elevated numbers or greater proximity of enhancer regulatory elements near the gene [ 3 , 127 ]. In medulloblastoma, enhancer-hijacking resulting from somatic structural variants has been demonstrated to activate the proto-oncogenes GFI1 and GFI1B [ 128 ].…”
Section: Carcinogenic Mechanism Of Structural Variationmentioning
confidence: 99%
“…Although numerous improvements have been made in gastric cancer (GC) diagnosis and treatment, GC still is the third most deadly cancer worldwide, especially in East Asia. [1][2][3][4] Thus, the further identification and validation of GC-associated genes, new pathways and therapeutic targets, drugs and strategies for combination therapy are urgently needed.…”
Section: Introductionmentioning
confidence: 99%